2009
DOI: 10.1128/aem.00859-09
|View full text |Cite
|
Sign up to set email alerts
|

rhs Genes Are Potential Markers for Multilocus Sequence Typing of Escherichia coli O157:H7 Strains

Abstract: DNA sequence-based molecular subtyping methods such as multilocus sequence typing (MLST) are commonly used to generate phylogenetic inferences for monomorphic pathogens. The development of an effective MLST scheme for subtyping Escherichia coli O157:H7 has been hindered in the past due to the lack of sequence variation found within analyzed housekeeping and virulence genes. A recent study suggested that rhs genes are under strong positive selection pressure, and therefore in this study we analyzed these genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 43 publications
(73 reference statements)
4
28
1
Order By: Relevance
“…Moreover, a strong association between clade 8 and lineages I/II was observed where all clade 8 strains were represented by lineage I/II and were absent in the other lineages. A similar observation was reported by other studies Liu et al, 2009;Hartzell et al, 2011) supporting the previous postulation that within lineage I/II, certain clades are more virulent and are responsible for more frequent and severe diseases than others Vanaja et al, 2010). Furthermore, these findings provided more evidence that clade 8 might be used as a useful surrogate genotype for the highly virulent lineage I/II strains.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, a strong association between clade 8 and lineages I/II was observed where all clade 8 strains were represented by lineage I/II and were absent in the other lineages. A similar observation was reported by other studies Liu et al, 2009;Hartzell et al, 2011) supporting the previous postulation that within lineage I/II, certain clades are more virulent and are responsible for more frequent and severe diseases than others Vanaja et al, 2010). Furthermore, these findings provided more evidence that clade 8 might be used as a useful surrogate genotype for the highly virulent lineage I/II strains.…”
Section: Discussionsupporting
confidence: 79%
“…Our results revealed that the remaining lineage I/II strains were representatives of clades 5, 6 and 7. Clade 6 and 7 strains have been previously noted among US O157 strains that were designated to be represented by lineage I/II (Liu et al, 2009). To the best of our knowledge, this study provides the first evidence of clade 5 association with lineage I/II.…”
Section: Discussionsupporting
confidence: 48%
“…The clade 8_rhsA assay targets one of the single nucleotide polymorphisms (SNPs) possible in the rhsA gene (SNP position 3468) (29). A PCR fragment with a length of 635 bp was generated with the rhsA primers indicated in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This structure suggests that rhs genes are composites formed by the insertion of horizontally transferred core-extension sequences (2,3). Rhs-CT polymorphism is extensive, and different strains of a given species typically contain a distinct complement of rhs alleles (2,3,5). Rhs are distributed throughout β-, γ-, and δ-proteobacteria, and genes encoding more distantly related YD-peptide repeat proteins are found in Gram-positive bacteria, some fungi, and higher metazoans through the vertebrates (6)(7)(8).…”
mentioning
confidence: 99%